Differential effects of oral and transdermal postmenopausal estrogen replacement therapies on C-reactive protein - Lacut, Karine; Oger, Emmanuel; Le Gal, Grégoire; Blouch, Marie-Thérèse; Abgrall, Jean-François; Kerlan, Véronique; Scarabin, Pierre-Yves; Mottier, Dominique; and the SARAH investigators (Thrombosis and Haemostasis, 2003)
C-reactive protein (CRP) is one of the main independent predictors of cardiovascular events. Oral post-menopausal estro-gen replacement therapy (ERT) increases CRP levels, but the effect of transdermal ERT is not well documented.CRP, interleukine-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels were evaluated in a randomised study of 196 healthy postmenopausal women, who were allocated to receive continuous oral estradiol-17β, (n=63) or transdermal estradiol-17β, (n=68) both combined with micronised progesterone, or placebo (n=65). Oral estrogen increased CRP levels compared with both placebo (p=0.010) and transdermal estrogen (p=0.004) at 6 months. There was no significant effect of transdermal estro-gen on CRP levels compared with placebo (p=0.997). No significant difference was found in the median changes for IL-6 and TNF-α between the three treatment groups.In conclusion, transdermal estrogen has no significant effect on CRP levels at 6 months, but CRP concentrations increased significantly with oral estrogen although no changes in cytokine levels were detected. The clinical relevance of these effects remains to be determined.
Keywords: Oral estrogen replacement therapy; transdermal estrogen replacement therapy; inflammation; C-reactive protein; interleu-kine-6; tumor necrosis factor alpha; randomised trial